The Impact of Long-Term Care Policy on the Percentage of Older Adults With Disabilities Cared for by Family Members in China: A System Dynamics Simulation. (March 2021) - Peng, Rong; Wu, Bei
This study examined the impact of current and future long-term care (LTC) policies on the family caregiving burden in China. System dynamics (SD) methodology was used to construct an LTC delivery system model that simulates the demand of LTC, living options, and LTC service use for disabled older adults. The model was based on three policy variables including the proportion of payment from LTC insurance, the growth rate of beds in LTC institutions, and the time to adjusting the capacity of community-based care. Results showed that the percentage of older adults with disabilities cared for by family members was projected to increase from 92.6% in 2015 to 97.8% in 2035, assuming no policy changes; under the mixed policy scenario, this percentage would reduce significantly to 63.8% in 2035. These findings illustrate that changes in LTC policy and delivery system have a significant impact on family care.